Changes in language use mediate expressive writings benefits on Health-Related Quality of Life (HRQOL) following Myocardial Infarction - Hevey, David (My University, 2014)
The present study assessed linguistic mediators on the effects of expressive writing on health-related quality of life (HRQOL), depression and anxiety following myocardial infarction (MI). One hundred and twenty-one cardiac patients were randomised (expressive writing = 61; control = 60), 98 (expressive writing = 47; control = 51) provided pre- and post-data, with 89 (expressive writing = 43; control = 46) completing the three-month follow-up. The expressive writing group wrote (20 mins/day for three consecutive days) about their thoughts and feelings regarding their MI, and the control group wrote (20 mins/day for three consecutive days) about daily events that occurred during the year prior to the MI. The outcome measures of depression, anxiety and HRQOL were completed pre-randomisation, post-intervention and three months post-intervention; the mediating variables assessed were changes in (a) positive emotion words, (b) negative emotion words and (c) cognitive-processing words. Three months post-intervention, the expressive writing group had significantly higher HRQOL. The positive effects of expressive writing were significantly associated with increases in both positive emotion words and cognitive-processing words across the three days of expressive writing. Expressive writing is a beneficial intervention that may enhance HRQOL among cardiac patients.
PUBLISHED
Keywords: health-related quality of life